Rational design and implementation of a cucurbit[8]uril-based indicator-displacement assay for application in blood serum. Issue 27 (26th June 2019) - Sinn, Stephan; Spuling, Eduard; Bräse, Stefan; Biedermann, Frank
Abstract : In this study, we report the first supramolecular indicator displacement assay (IDA) based on cucurbit[ n ]uril (CB n ) host and a [2.2]paracyclophane derivative as indicator that is operational in blood serum. Abstract : In this study, we report the first supramolecular indicator-displacement assay (IDA) based on cucurbit[ n ]uril (CB n ) hosts that is operational in blood serum. Rational design principles for host–guest chemosensing in competitively binding media were derived through detailed mathematical simulations. It was shown that currently known CB n -based chemosensing ensembles are not suited for use in highly competitive matrices such as blood serum. Conversely, the simulations indicated that a combination of cucurbit[8]uril (CB8) and an ultra-high affinity dye would be a promising IDA reporter pair for the detection of Alzheimer's drug memantine in blood serum. Therefore, a novel class of [2.2]paracyclophane-derived indicator dyes for the host CB8 was developed that possesses one of the highest host–guest affinities ( K a > 10 12 M −1 in water) known in supramolecular host–guest chemistry, and which provides a large Stokes shift (up to 200 nm). The novel IDA was then tested for the detection of memantine in blood serum in a physiologically relevant sub- to low micromolar concentration range.